Analisis Tingkat Literasi Lingkungan Mahasiswa Penghuni Kos di Kecamatan Medan Tembung - Laura Aulia Silalahi; Mahfuzi Irwan; Hayunda Aura Sifa; Sabila Alvina (CV. Eracita Grup, 2026)
This study aims to analyze the level of environmental literacy among university students living in boarding houses in Medan Tembung District and to examine the role of the boarding house environment in supporting pro-environmental behavior. This research employed a quantitative approach with a descriptive survey design involving 60 respondents selected using accidental sampling. Data were collected through a Likert-scale questionnaire measuring environmental knowledge, attitudes, and behaviors, and analyzed using descriptive statistics. The results indicate that the environmental literacy level of boarding house students is categorized as good across all measured dimensions. Environmental attitudes and support from the boarding house environment show the highest average scores, while pro-environmental behavior, although still categorized as good, appears relatively lower. These findings suggest that students’ environmental behavior is influenced not only by individual factors but also by the availability of facilities and the management of the boarding house environment. This study concludes that the boarding house environment plays a crucial role in supporting the implementation of students’ environmental literacy. Therefore, improving sanitation facilities and strengthening environmental management in boarding houses are recommended to promote sustainable pro-environmental behavior among students.